Hypertension, emotions and happiness: A brief view from the biology to the positive psychology (2022)
High blood pressure (HBP) is a silent disease with an extremely high prevalence worldwide. It is considered the leading risk factor for cardiovascular (CVD) and neurovascular disorders. The etiology of hypertension is based on various genetic, environmental, and social factors. Currently, compelling evidence points to the link between HBP and certain psycho-emotional factors, such as mental stability, happiness, general well-being, and fulfillment, all consistently associated with better physical and psychological health. Clinical and epidemiological evidence supports their value as a novel target in HBP management despite the lack of clarity concerning how psycho-emotional and affective states affect cardiovascular health. Among the main psycho-emotional strategies implemented to treat HBP and other CVD patients, emphasis should be placed on psychosocial interventions and positive psychology, which have shown promising results in this regard thus far. Therefore, this review aims to comprehensively determine whether an individual’s psychosocial and emotional state can be an HBP risk factor.